Evidence of mesenchymal stromal cell adaptation to local microenvironment following subcutaneous transplantation. Issue 18 (12th August 2020) - Preda, Mihai Bogdan; Lupan, Ana‐Mihaela; Neculachi, Carmen Alexandra; Leti, Livia Ioana; Fenyo, Ioana Madalina; Popescu, Sinziana; Rusu, Evelyn Gabriela; Marinescu, Catalina Iolanda; Simionescu, Maya; Burlacu, Alexandrina
Abstract: Subcutaneous transplantation of mesenchymal stromal cells (MSC) emerged as an alternative to intravenous administration because it avoids the pulmonary embolism and prolongs post‐transplantation lifetime. The goal of this study was to investigate the mechanisms by which these cells could affect remote organs. To this aim, murine bone marrow–derived MSC were subcutaneously transplanted in different anatomical regions and the survival and behaviour have been followed. The results showed that upon subcutaneous transplantation in mice, MSC formed multicellular aggregates and did not migrate significantly from the site of injection. Our data suggest an important role of hypoxia‐inducible signalling pathways in stimulating local angiogenesis and the ensuing modulation of the kinetics of circulating cytokines with putative protective effects at distant sites. These data expand the current understanding of cell behaviour after subcutaneous transplantation and contribute to the development of a non‐invasive cell‐based therapy for distant organ protection.